(untitled) (Law, State and Telecommunications Review, 2009)
Communication systems are now converging, but communication policy has evolved to treat different media with different doctrines. Most solutions for a post-convergence communication policy are adjustments to inherited regulatory categories. Instead, this article revisits the underlying goals of policymaking across all media. First, this article presents a conceptual model for the communication policy process as one of inertia punctuated by crisis. Second, it applies this model to a very brief history of policy in the US, considering print, post, telephony, broadcasting, and the Internet. Third, from this analysis it suggests useful approaches in a converged environment, distinguishing three underlying goals for policy: the right to publish, the right to private exchange, and the right to design communication platforms.